Intentions and Realities in Doctoral Education in Norway. New Policies for Doctoral Education in Norway and the Implications for an Inter-Institutional Research School (WNGER II)—Some Preliminary Findings - Krumsvik, Rune Johan (Frontiers in Education, 2022)
This policy and practise review article examines how new policies and policy documents impact a graduate-level research school in Norway, Western Norway Graduate School of Educational Research II (WNGER II) on a general level. WNGER II is a research school consortium with seven universities and university colleges, six PhD programmes, 97 PhD candidates, and 48 supervisors. It was established in 2018 to complement existing PhD programmes and strengthen PhD education in Western Norway. A pilot phase (2016–2017) was used to identify and address specific challenges in PhD education as experienced in the seven universities and university colleges of Western Norway. Against this backdrop, this policy and practise review article builds on our previous research on doctoral-level education and aims to illuminate the more general learning and teaching conditions in the WNGER II consortium in light of national PhD regulations. This subject will be examined in light of the relationships among the arenas of formulisation (macro-level), transformation (meso-level), and realisation (micro-level). Frame factor theory is used as a lens to examine how new policies impact the doctoral level of higher education, and the main data source of the study is document analysis. The policy and practise review shows that the new national policies on doctoral education add a new layer of requirements on several levels, a situation that can be demanding and challenging for institutions and might be considered part of what has come to be known as a certain tendency toward “public management” within higher education. Such new policies and requirements constitute changing frame factors, which can enhance the focus on educational, study, and teaching quality at the doctoral level in WNGER II. For some institutions, such as research schools, it seems particularly fruitful to deal with challenges through collaborative measures. A general finding seems to be that if WNGER II (and similar research schools) is to optimise its potential as a collaborative research school, increased integration amongst its six different PhD programmes is required. The study finds that certain actionable recommendations could be relevant to consider in relation to the institutions' frame factors to facilitate further development of the research school. There are also several limitations on the study, since this is the first phase of formative dialogue research and only deals with a general policy review. Therefore, the findings should be interpreted with great caution.